Three new genera and four new species of aleocharine staphylinids with unusually long mandibles from Australia (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) - Ashe, James S. (Zootaxa, 2005)
This paper describes three distinctive, closely related, new genera and four species of Homalotini (Aleocharinae: Staphylinidae) characterized by extremely long slender, curved mandibles, very long slender and whip-like setae variously placed on the labrum, clypeus, or mentum; and similarities in the mouthparts, aedeagi and spermathecae. These new taxa are Eumecognathus new genus, type species E. tasmaniensis new species (type locality: SW Tasmania, Lower Gordon River); Siagotanyx new genus, type species S. rufa new species (type locality: Tasmania, Lake St. Claire National Park) and Drepanomastax new genus, type species D. splendida new species (type locality: Australian National Territory, Mt. Ainslie). Also described is D. nitida new species (type